2017
DOI: 10.3144/expresspolymlett.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of natural rubber reinforced with polydopamine-coating modified carbon nanotubes

Abstract: IntroductionNR is one of the most important nature polymers, which is widely used as the elastomeric matrix of various materials, including conveyor belts, sealing rings, tires, etc. In order to meet the requirements of the use of tires, NR composites must have the following two properties: (1) good mechanical properties, in order to undergo cyclic loading and strains in actual use, (2) good thermal conductivity and electrical conductivity, in order to export the heat or static electricity effectively and time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Furthermore, the motion of long alkyl chains of PHS also created more free volume in the polymer, which played a certain role in the lubrication. Tensile testing and hardness testing, which could be used to determine the mechanical properties of materials were used to investigate the polymer plasticity . With increasing PHS amount, its effects on three kinds of mechanical properties of PVC were different.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the motion of long alkyl chains of PHS also created more free volume in the polymer, which played a certain role in the lubrication. Tensile testing and hardness testing, which could be used to determine the mechanical properties of materials were used to investigate the polymer plasticity . With increasing PHS amount, its effects on three kinds of mechanical properties of PVC were different.…”
Section: Resultsmentioning
confidence: 99%
“…Tensile testing and hardness testing, which could be used to determine the mechanical properties of materials were used to investigate the polymer plasticity. 23,24 With increasing PHS amount, its effects on three kinds of mechanical properties of PVC were different. The elongation at break and hardness of PVC-PHS decreased first and then increased with increasing PHS, whereas the tensile strength showed a reverse trend.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The formed PDA surface possesses highly reactive functional groups, and it can be used to enhance the compatibility of nanofillers and polymers. Thus, DA has emerged as a functional modifier of nanofillers in the field of polymer reinforced nanocomposites [ 19 , 20 , 21 , 22 ]. Y.L.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al incorporated PDA-modified, multi-walled carbon nanotubes (MWCNTs) into natural rubber (NR) via latex compounding. The modified carbon nanotubes showed excellent dispersion in the matrix, increasing the tensile strength of the composite by 42% [ 20 ]. Y. Fang et al prepared polyimide (PI) with polydopamine functionalization boron nitride nanosheets composite fiber by in situ polymerization, and the results indicated that the tensile strength and modulus of the composite fiber were a significant improvement with the addition of modified boron nitride nanosheets (0.5 wt% content) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are usually poor compatibility and interface adhesion between nano‐SiO 2 and rubber matrix, which results in poor dispersibility of nano‐SiO 2 in the rubber matrix and hinders its application in tire industry 8–10 . This drawback, fortunately, could be eliminated by surface‐capping nano‐SiO 2 with silane coupling agent, 11,12 ionic liquid, and compatibilizer 13–20 . For example, Sung‐seen choi 21 found that chloroprene rubber could improve the dispersion of silica in natural rubber, which is attributed to the hydrogen bond interaction between silicon hydroxyl and chloride group.…”
Section: Introductionmentioning
confidence: 99%